2020
DOI: 10.1002/ecy.3120
|View full text |Cite
|
Sign up to set email alerts
|

Evolution in novel environments: Do restored prairie populations experience strong selection?

Abstract: When populations colonize new habitats, they are likely to experience novel environmental conditions, and as a consequence may experience strong selection. While selection and the resulting evolutionary responses may have important implications for establishment success in colonizing populations, few studies have estimated selection in such scenarios. Here we examined evidence of selection in recently established plant populations in two prairie restorations in close proximity (<15 km apart) using two approach… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Trade‐offs between other traits also could limit adaptation in Marshall but not Lux if selection favors different traits at the two sites or if the expression of genetic covariances differs across sites (environmental effects on the G‐matrix, Wood & Brodie, 2015). While previously observed differences in trait values between the Lux and Marshall populations suggest that selection differed between populations in the past, an earlier study detected little evidence that current selection differs across site (Magnoli & Lau, 2019) or that G‐matrices vary across populations (unpublished data, S.M.M.). Swamping effects of gene flow are also unlikely to limit adaptation, because there are no other known naturally occurring Chamaecrista populations in the surrounding landscape.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Trade‐offs between other traits also could limit adaptation in Marshall but not Lux if selection favors different traits at the two sites or if the expression of genetic covariances differs across sites (environmental effects on the G‐matrix, Wood & Brodie, 2015). While previously observed differences in trait values between the Lux and Marshall populations suggest that selection differed between populations in the past, an earlier study detected little evidence that current selection differs across site (Magnoli & Lau, 2019) or that G‐matrices vary across populations (unpublished data, S.M.M.). Swamping effects of gene flow are also unlikely to limit adaptation, because there are no other known naturally occurring Chamaecrista populations in the surrounding landscape.…”
Section: Discussionmentioning
confidence: 91%
“…Compared to the Marshall site, the Lux site has lower available soil nitrogen (1.3 g N/kg and 2.3 g N/kg at Lux and Marshall, respectively), lower soil phosphorus (23.78 ppm and 54.54 ppm, respectively), and higher percent soil moisture. A previous study of these Chamaecrista populations found evidence of genetic differentiation between populations in flowering time (the Lux population flowers earlier than the Marshall population, which flowers earlier than the original source population), root nodule formation, and specific leaf area (the Lux population is more likely to produce root nodules than the Marshall population and has significantly lower SLA than the original population; Magnoli & Lau, 2019), suggesting that these populations have undergone evolutionary changes over the six years since they were established.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation